Peningkatan Personal hygiene Pekerja Keramba Jaring Apung Melalui Pemanfaatan Sumber Air Clean Water Filtration di Desa Paropo I, Kabupaten Dairi - Sri Malem Indirawati; Umi Salmah; Nurmaini Nurmaini; Azrasha Hanna Febri Mawaddah; Bethani Novi Tessalonika; Hiskia D’timosky Pratama (Shihatuna : Jurnal Pengabdian Kesehatan Masyarakat, 2025)
Residents of Paropo I Village face serious challenges accessing clean water due to Lake Toba's declining quality and reduced mountain spring flow, especially during the rainy season. KJA (Keramba Jaring Apung) workers often use untreated lake water for hygiene, increasing dermatitis cases. A community service program was developed to address this issue, supporting SDGs 3 and 6 by promoting environmental stewardship and appropriate clean water technologies. Previous research identified underutilization of clean water facilities (CWF) due to low public awareness and poor maintenance. The program fosters behavior change and public health improvement through community engagement, educational videos, and mentoring KJA workers on hygiene practices. It also strengthens local capacity via the PANRAIR (Pantau dan Rawat Air Bersih) initiative, empowering KJA owners to lead sustainable CWF management. Expected outcomes include better sanitation knowledge, improved hygiene, and stronger governance. Outputs include media coverage, educational content, and increased community participation. Partners contribute by offering meeting spaces and mobilizing support for CWF revitalization